Medications for Opioid Use Disorder in State Prisons: Perspectives of Formerly Incarcerated Persons. Issue 1 (December 2022) - Treitler, Peter C.; Enich, Michael; Reeves, Donald; Crystal, Stephen
Background : Opioid use disorder (OUD) is common among incarcerated persons and risk of overdose and other adverse drug-related consequences is high after release. Recognizing their potential to reduce these risks, some correctional systems are expanding access to medication for opioid use disorder (MOUD). This study explored the experiences and perspectives of formerly incarcerated individuals on MOUD use while incarcerated and after release. Methods : We interviewed 53 individuals with self-reported OUD who were released from New Jersey state prisons. Interviews explored motivations to use MOUD while incarcerated and after release, and experiences with prison-based MOUD and transition to community-based care. We performed cross-case analysis to examine common and divergent perspectives across participants. Results : A common reason for accepting prerelease MOUD was recognition of its effectiveness in preventing drug use, overdose, and other drug-related consequences. Participants who chose not to use MOUD often were focused on being completely medication-free or saw themselves as having relatively low-risk of substance use after a prolonged period without opioid use. A few participants reported challenges related to prison-based MOUD, including logistical barriers, stigma, and once-daily buprenorphine dosing. Most participants effectively transitioned to community-based care, but challenges included insurance lapses and difficulty locating providers. Conclusions : Many formerly incarcerated persons with OUD recognize the value of MOUD in supporting recovery, but some hold negative views of MOUD or underestimate the likelihood that they will return to drug use. Patient education on risks of post-release overdose, the role of MOUD in mitigating risk, and MOUD options available to them could increase engagement. Participants' generally positive experiences with MOUD support the expansion of correctional MOUD programs.